2005
DOI: 10.1300/j041v18n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Parent' Reactions to Transgender Youth' Gender Nonconforming Expression and Identity

Abstract: Fifty-five transgender youth described their gender development and expression, parents' reactions to their gender nonconformity, and initial and current mothers' and fathers' reactions to their transgender identity. All of the youth reported feeling different from others in early childhood. Forty-three of the participants' mothers and 26 of their fathers knew about their identities. The youth reported that 54% of their mothers and 63% of their fathers initially reacted negatively, and 50% of the mothers and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 12 publications
4
127
1
7
Order By: Relevance
“…Acceptance in this study seemed to be couched more in terms of how others might view and 'accept' their child, rather than how the parents themselves accepted their child which has been the reported findings of other research (Grossman et al, 2005;Hegedus, 2009 untypical. Given the often conflicting and ambiguous narrative presented in the interviews, there is a possibility that the concern about others accepting their child is in fact a projection of their own unwanted feelings.…”
Section: Sometimes I Think How Do I Justify Me Not Encouraging It Butmentioning
confidence: 55%
See 1 more Smart Citation
“…Acceptance in this study seemed to be couched more in terms of how others might view and 'accept' their child, rather than how the parents themselves accepted their child which has been the reported findings of other research (Grossman et al, 2005;Hegedus, 2009 untypical. Given the often conflicting and ambiguous narrative presented in the interviews, there is a possibility that the concern about others accepting their child is in fact a projection of their own unwanted feelings.…”
Section: Sometimes I Think How Do I Justify Me Not Encouraging It Butmentioning
confidence: 55%
“…Grossman et al (2005) found that the fathers who had been informed were more likely than the mothers to react negatively to their child's gender nonconformity, and the more extreme the nonconformity, the more likely the young person was to be verbally and physically abused by their parents.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Zowel stigmatisering als negatieve ervaringen met familie en ouderlijke afwijzing zijn een mogelijke verklaring voor de moeilijkheden waar transgenderjongeren mee worden geconfronteerd (Grossman, D'Augelli, Howell, & Hubbard, 2005;Meyer, 2003). Daarnaast blijkt dat andere kinderen negatief reageren op atypisch gendergedrag (Signorella, Bigler, & Liben, 1993;Ruble et al, 2007;Smetana, 1986) en is bekend dat pestgedrag tijdens de kindertijd nega-tieve gevolgen heeft voor de ontwikkeling van het kind (Bond, Carlin, Thomas, Rubin, & Patton, 2001;Sourander et al, 2007).…”
Section: Ervaren Stigmatisering En Sociale Steun Bij Jonge Transgendersunclassified
“…La négociation d'un passage vers cette nouvelle identité s'inscrit dans un processus d'adaptation (D'Augelli, 2005). Certaines études ont comparé ce processus à celui d'un deuil, évoquant le cadre d'analyse en cinq étapes développé à l'origine par Kübler-Ross (1969) où le choc, le déni, la colère et la négociation se succèdent pour mener finalement à l'acceptation.…”
Section: Vers Une Nouvelle Identité Parentale Et Familiale « Je Suis unclassified
“…Les recherches démontrent que l'acceptation et le soutien parental sont des facteurs de protection contre les effets négatifs de la victimisation sur le bien-être et la santé mentale des jeunes gais et lesbiennes (D'Augelli et al, 2005 ;Needham et Austin, 2010 ;Padilla et al, 2010). À cet égard, les parents ont un rôle important à jouer auprès de leur enfant (Goldfried et Goldfried, 2001).…”
Section: Introductionunclassified